2016
DOI: 10.3389/fmicb.2016.01120
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a New Cold-Adapted and Salt-Activated Polysaccharide Lyase Family 7 Alginate Lyase from Pseudoalteromonas sp. SM0524

Abstract: Marine bacterial alginate lyases play a role in marine alginate degradation and carbon cycling. Although a large number of alginate lyases have been characterized, reports on alginate lyases with special characteristics are still rather less. Here, a gene alyPM encoding an alginate lyase of polysaccharide lyase family 7 (PL7) was cloned from marine Pseudoalteromonas sp. SM0524 and expressed in Escherichia coli. AlyPM shows 41% sequence identity to characterized alginate lyases, indicating that AlyPM is a new P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 43 publications
1
70
1
Order By: Relevance
“…AlgSH7 contains an QIH sequence, while, it prefers polyM blocks. This result is similar to AlyA-OU02, AlyPM, and FlAlyA [24][25][26]. Most of the reported PL7 family alginate lyases have endolytic activity.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…AlgSH7 contains an QIH sequence, while, it prefers polyM blocks. This result is similar to AlyA-OU02, AlyPM, and FlAlyA [24][25][26]. Most of the reported PL7 family alginate lyases have endolytic activity.…”
Section: Discussionsupporting
confidence: 82%
“…AlgSH7 contains 642 amino acids with a theoretical molecular mass of 66.4 kDa and theoretical pI 4.71. AlgSH7 belongs to the PL7 family because it contains the SA3 domain (RTELR), the SA4 domain (YFKAGVYNQ), and the SA5 catalytic domain (QIH), which are conserved in the aligned catalytic modules of PL7 family alginate lyase [21,25]. Among the characterized alginate lyases derived from the Microbulbifer genus, AlgSH7 is 83.6% homologous with alginate lyase AlgMsp (BAJ62034.1) and 73.22% homologous with alginate lyase AlyM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The alignment indicated that Aly1281 was most closely related to alginate Lyase (PDB ID: 4BE3_A) from Zobellia galactanivorans with an amino acid sequence identity of 42.4%. Aly1281 contained three highly conserved regions of PL family 7, namely, R(S/T)ELV(R/G), QIH, and YFK(A/L)GAYNQ, which played an important role in the substrate binding and catalytic activity of the enzymes [15,17,20]. Moreover, catalytic (Q173, H175, and Y315) and substrate binding (R104, E194, K197, E216, D228, and W327) sites were predicted in Aly1281 on the basis of previous research on alginate lyase (AlyA5) from Z. galactanivorans [21].…”
Section: Aly1281 Gene and Protein Sequence Informationmentioning
confidence: 99%